SURGICAL MANAGEMENT OF TESTICULAR HYPERPLASIA IN A CRYPTORCHID LABRADOR RETRIEVER - MOMIN, T M; KELAWALA, D N; SUTHAR, V S; PATIL, D B (The Indian Journal of Animal Reproduction, 2022)
A 6-year-old Labrador retriever was presented with subcutaneous inguinal mass increasing in size. On scrotal palpation, the dog was bilaterally cryptorchid. Ultrasonography revealed mixed echogenic enlarged testicle, while the other could not be visualized. The surgical removal of subcutaneous testicular mass was done with uneventful recovery.